When the poor buy the rich: New evidence on wealth effects of cross-border acquisitions - Ho Hong Hai; Vu Thi Hanh; Ngoc-Tien Dao; Manh-Tung Ho; Quan Hoang Vuong (Journal of Risk and Financial Management, 2019)
The growing trend of merging and acquisition (M&A) investments from emerging to developed market economies over the last two decades motivates the question on the long-run effects of M&A on the wealth of emerging markets. This paper contributes to the current literature on cross-border M&A (CBMA) by focusing on the long-term effects of this event on the bidder's stock return in emerging markets. To address the challenges of finding an accurate measure for the effects, this study applies the propensity score matching framework in tandem with difference-in-differences (DID) on a comprehensive dataset over the 1990-2010 period. The analyses show evidence of systematic detrimental impacts of cross-border M&A on shareholders' welfare in the long run, to a certain extent, diverging from the existing literature, which mainly highlights the positive effects for certain types of M&A. The striking finding is that such strong negative effects remain persistent even when various factors previously known as capable of suppressing underperformance are considered. Our study is in line with the growing landscape of cross-border mergers and acquisitions from the "poor" to the "rich" countries.
Keywords: 330; M&A; wealth effects; propensity score matching; emerging markets